Root Necrosis of Strawberries Caused by Colletotrichum acutatum - J. C. Mertely; N. A. Peres (EDIS, 2005)
Colletotrichum acutatum is widely known as a fruit rot pathogen, but also infects other strawberry tissues, including the roots. Root necrosis has been observed in Florida since 2000.  This document is PP-211, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date August 2005.